(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article provides information about the remains of a family bathhouse found at the Tunkat monument. Tunkat was an economic and industrial center in the Ohangaron Valley during ancient and medieval times. The article highlights the structure of the bathhouse uncovered during excavations, the ceramic artifacts found, and the sanitary and cultural significance of the bath. The discovery of this family bathhouse from the Karakhanid period indicates that the residents of Tunkat paid great attention to cleanliness and sanitary practices. This article contributes to expanding scientific and historical knowledge about the bathhouses of that era.